Severe pre-eclampsia: epidemiological, diagnostic, therapeutic and prognostic aspects at Hospital Principal Dakar from January 2019 to December 2020 - Gaye, Yaye F. O.; Seck, Mame D.; Ngom, Papa M.; Sylla, Mafing A.; Niang, Ndama; Faye, Marie E.; Kone, Madjiguene; Fall, Mouhmadou M.; Fall, Khadija; Niang, Tagouthie (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Preeclampsia, major public health problem, is one of the leading causes of maternal and infant mortality. It is increasingly frequent in our referral health centers, especially in its severe form. Methods: Retrospective descriptive and analytical study about severe preeclampsia at the Maternity of Hospital Principal Dakar, from 01 January 2019 to 31 December 2020. Results: Frequency of severe preeclampsia was 3.09%. Medical evacuation (70.59%) was the most frequent mode of admission. Patients were in average 29.8 years and primipare. Personal medical history was dominated by high blood pressure (16.29%). The average gestational age was 34+2 days, but pregnancy was carried to term by the majority of patients. Functional signs were dominated by headache (40.65%). Blood pressure was greater than or equal to 160/90 mmHg (90.32%). Hyperuricemia was the most frequent biological anomaly after proteinuria (45.1%). Complications were dominated by retroplacental hematoma (4.49%) and intrauterine growth retardation (IUGR) (28.48%). Calcium channel blockers (81.88%) were the main antihypertensive agents administered. Caesarean section was the most common delivery method (80.46%). The maternal prognosis was good, with no maternal deaths recorded. Perinatal mortality was 173.9%. Conclusions: Preeclampsia remains a fearsome pregnancy’s pathology. Raising awareness of pregnant women during ANC on the risks of pre-eclampsia, retraining of health personnel, close and early monitoring of women at risk and management in a multidisciplinary setting help to improve the maternal-fetal prognosis.